A Population of Navigator Neurons is Essential for Olfactory Map Formation during Critical Period - Wu, Yunming (Neuron, 2018)
In the developing brain, heightened plasticity during the critical period enables the proper formation of neural circuits. Here we identify the “navigator” neurons, a group of perinatally born olfactory sensory neurons, as playing an essential role in establishing the olfactory map during the critical period. The navigator axons project circuitously in the olfactory bulb and traverse multiple glomeruli before terminating in perspective glomeruli. These neurons undergo a phase of exuberant axon growth and exhibit a shortened lifespan. Single cell transcriptome analyses reveal distinct molecular signatures for the navigators. Extending their lifespan prolongs the period of exuberant growth and perturbs axon convergence. Conversely, genetic ablation experiment indicates that, despite postnatal neurogenesis, only the navigators are endowed with the ability to establish a convergent map. The presence and the proper removal of the navigator neurons are both required to establish tight axon convergence into the glomeruli.